We gon' be alright notes on race and resegregation - Chang, Jeff (Picador, 2016)
"In his most recent book, Who We Be, Jeff Chang looked at how art and culture effected massive social changes in American society. Since the book was published, the country has been gripped by waves of racial discord, most notably the protests in Ferguson, Missouri. In these highly relevant, powerful essays, Chang examines some of the most contentious issues in the current discussion of race and inequality. Built around a central essay looking at the rise of the Black Lives Matter movement and the events in Ferguson, Missouri, surrounding the death of Michael Brown, Chang questions the value of "the diversity discussion" in an era of increasing racial and economic segregation. He unpacks the return of student protest across the country and reveals how the debate over inclusion and free speech was presaged by similar protests in the 1980s and 1990s. The author of Can't Stop Won't Stop looks at how culture impacts our understanding of the politics of this polarized moment. Throughout these essays Chang includes the voices of many of the leading activists as he charts how popular voices on the ground and in social media have catalyzed the push for protest and change."-- Provided by publisher
Keywords: Racism / United States; Segregation / United States; Equality / United States; Social change / United States; Cultural pluralism / United States; Multiculturalism / United States; Minorities / United States; Cultural pluralism; Equality; Minorities; Multiculturalism; Race relations; Racism; Segregation; Social change; Minderheit; United States / Race relations; United States; USA